2003
DOI: 10.1111/1468-0475.00082
|View full text |Cite
|
Sign up to set email alerts
|

A First Assessment of Some Measures of Core Inflation for the Euro Area

Abstract: Core inflation plays an important role in the deliberations of monetary policy-makers. In this paper we evaluate a number of measures of core inflation constructed using euro-area data. In addition to the traditional exclusion-type core measures, we examine two newer ones, documenting their properties and evaluating their performance in terms of their ability to track underlying or trend inflation in real time. We focus on core measures derived from the Harmonized Index of Consumer Prices (HICP) as the Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 23 publications
0
39
0
Order By: Relevance
“…In empirical studies and monetary policy analysis sometimes concepts of equilibrium and/or core inflation are added to (1), to distinguish shortrun fluctuations of inflation from longer term, equilibrium inflation. In our analysis this issue is not dealt with and inflation (as all other variables) is defined in terms of deviations from (possibly nonzero inflation) steadystate (see Vega and Wynne, 2003).3 We consider that the coefficient on pt is equal to one, which signifies that last period's inflation is very important for the formation of current inflation.…”
Section: Komlan Fiodendji 51mentioning
confidence: 99%
“…In empirical studies and monetary policy analysis sometimes concepts of equilibrium and/or core inflation are added to (1), to distinguish shortrun fluctuations of inflation from longer term, equilibrium inflation. In our analysis this issue is not dealt with and inflation (as all other variables) is defined in terms of deviations from (possibly nonzero inflation) steadystate (see Vega and Wynne, 2003).3 We consider that the coefficient on pt is equal to one, which signifies that last period's inflation is very important for the formation of current inflation.…”
Section: Komlan Fiodendji 51mentioning
confidence: 99%
“…Vega & Wynne (2003), Cecchetti (1997), Culter (2001), Bilke & Stracca (2007) found that food prices are relatively persistent in Euro area. There is a large-scale project of the Eurosystem entitled Inflation Persistence Network (EIPN) implemented during the period of 2003-2005 to analyse inflation persistence for the euro area.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A common problem faced by those responsible for monetary policy decisions is that standard measures of prices are often contaminated by three main types of transitory shocks: i) measurement errors, ii) regular seasonal fluctuations, and iii) other non-monetary factors, such as for example a good or bad harvest. This has prompted economists to suggest the use of 'filtered' versions of published price indexes as measures of underlying inflation, see for example Bryan and Cecchetti (1994) and Vega and Wynne (2001).…”
Section: Introductionmentioning
confidence: 99%
“…The first approach exploits the cross section dimension, and in effect acts upon the original series by modifying the weights attached to its different subcomponents. An example in this vein is a study conducted for the euro area HICP by Vega and Wynne (2001) which suggested that a trimmed mean measure of underlying inflation outperforms a measure computed by excluding unprocessed food and energy prices. The second approach exploits the time series dimension of the price index series, and builds a measure of underlying inflation at a point in time as the weighted sum of observations from the past and the future.…”
Section: Introductionmentioning
confidence: 99%